Hubungan pengetahuan ibu tentang imunisasi terhadap kelengkapan imunisasi dasar pada balita di wilayah Kerja puskesmas dumai kota kelurahan dumai kota - Hijani, Razana -; Nauli, Fathra Annis; Zulfitri, Reni - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research is to find out relationship between mother’s knowledge about immunization towards the complete basic immunization for toddlers at Dumai Kota Community Health Center Dumai Kota Village. This research used descriptive correlative with cross sectional approach. Sample of this research taken using purposive sampling. This research’s sample composed of 100 mothers who live in Dumai Kota village, Dumai. Data were collected using scale that have been tested for validity. Data then analyzed using chi-square with significance level of α 0,05. The results showed that both group of the mothers who have complete basic immunization for child 60 respondent (78.8%) and mother who do not have complete basic immunization for child 18 respondent (75%) (p value 0,000 > α 0,05). In conclusion, there is relationship between between mother’s knowledge about immunization towards the complete basic immunization for toddlers at Dumai Kota Community Health Center Dumai Kota Village. Based on this research suggested the family to support the mother to give basic immunization in children to prevent certain disease. Keywords : immunization, basic immunization, knowledge